Aged polyethylene microplastics and glyphosate-based herbicide co-exposure toxicity in Pacific white shrimp (Litopenaeus vannamei) - Thammatorn, Worrayanee; Cholewińska, Paulina; Kruangkum, Thanapong; Palić, Dušan (Frontiers in Marine Science, 2024)
Microplastics and glyphosate-based herbicides (GBHs) unavoidably contaminate aquatic environments, yet their combination effect on aquatic organisms has been scarcely investigated. We present the short-term study on individual and combined effects of aged polyethylene (PE) microplastics and GBH exposures at environmentally relevant concentrations on oxidative damage (malondialdehyde), antioxidant responses (superoxide dismutase and catalase), immune parameters (total hemocyte count, phenoloxidase activity, and immune-related genes), and hepatopancreas histology in shrimp (Litopenaeus vannamei). In addition, the acetylcholinesterase (AChE) was evaluated as a biomarker of GBH exposure. After 96 hours of exposure, individual PE microplastics exposure slightly influenced oxidative status, immune parameters, and histology. The decrease on AChE concentration and alterations of oxidative status, immunity, and cell population in hepatopancreas were observed in single GBH-exposed shrimp. The combinations of aged PE microplastics and GBH induced some changes that differed from individual GBH exposures. For instance, some alterations implied that the presence of aged PE microplastics may alleviate alter GBH toxicity to L. vannamei (AChE concentration and some expressions of immune-related genes). In conclusion, our results suggest that single exposure of aged PE microplastics at environmental concentration may slightly affect the health of L. vannamei and aged PE microplastics are likely to modify the toxicity of other co-exposed chemicals. Further research on the long-term toxicology test of and mechanism between microplastics and chemicals combination is needed.